Filogeografia e diversidade genética de tartarugas marinhas da costa semiárida do Atlântico Equatorial Ocidental baseada em sequências de DNA mitocondrial e nuclear - Monteiro, Cibele Castro (2024)
The coastline of Ceará stands out as an important region for sea turtles, including records of nesting sites, feeding grounds, and its identification as a migratory route. However, the role and degree of connection of sea turtles from the Ceará coast within the context of global turtle populations remain unclear. Genetic studies have provided significant advances in ecological information about this group. Nevertheless, analyses have so far predominantly focused on mitochondrial genes, which may be insufficient to address questions of connectivity and interspecies interactions. In this study, mitochondrial (COI) and nuclear (RAG1, RAG2) genetic material amplified by conventional PCR was used for analyses of stranded sea turtle samples collected during monitoring along the eastern coast of Ceará by the Association for Research and Conservation of Aquatic Ecosystems (AQUASIS) between 2010 and 2022. According to the Aquatic Biota Monitoring System (SIMBA), the region primarily reports occurrences involving the green turtle. The amplified DNA was sequenced using the Sanger method, yielding 102 sequences for the species Chelonia mydas (n=88), Caretta caretta (n=6), Eretmochelys imbricata (n=4), and Lepidochelys olivacea (n=4). These sequences were analyzed alongside 80 sequences available in the GenBank database. The available sequences were mostly for the species C. mydas and derived from mitochondrial DNA, which limits insights into genetic characteristics contributed by males. This information is particularly significant for the group, which exhibits a polyandrous mating system. The genomic database contains little or no sequence information for the studied species and genes, especially regarding nuclear sequences. The results indicate that sea turtles from populations collected in Ceará share haplotypes with other locations in the Atlantic Ocean, including samples from French Guiana, Puerto Rico, and the USA, as well as from the Pacific Ocean, such as samples from Australia and the Mediterranean Sea. The turtles also exhibit unique haplotypes specific to the region in both nuclear and mitochondrial analyses. For the RAG1 and RAG2 genes, some haplotypes were shared among different species from various locations. This provides information about the potential for genetic exchange between species, suggesting that the use of additional nuclear genes along with mitochondrial genes is essential to better understand the genetic stocks contributed by both females and males. Sample groups from different geographic regions appear to be genetically connected, with the possibility of gene flow facilitated by the migratory behavior of these species, even across oceans, or through the sharing of ancestral genes among these locations. Highly conserved regions were identified across different species, indicating genetic proximity, which may favor the occurrence of introgression within the group. This study highlights the importance of the northeastern region of Brazil for sea turtle conservation, as it hosts individuals at different life stages and, due to its genetic connectivity with other regions, could also be affected by external impacts.